The perception concerning the COVID-19 pandemic: case of Turkey - Hoşgör, Haydar; Aközlü, Zeynep; Gündüz Hoşgör, Derya (The European Research Journal, 2021)
Objectives: This study aims to evaluate the level of knowledge and perception of the Turkish society about the COVID-19 pandemic. Methods: This cross-sectional study whose sampling consists of 903 adults. Results: About half (49.6%) of the participants' information sources about COVID-19 composed of printed and visual media tools such as television, radio, newspaper, etc. 57.5% of the participants stated that their self-knowledge levels about COVID-19 were at a good level, whereas 19.7% of them at a very good level. 64.4% of the participants stated that their health would be seriously damaged if they get this virus; 58.9% of them thinks that this virus will severely damage their place of the resident; 50.9% of them stated that they trust that this crisis will be handled effectively by the health authorities of Turkey. Participants rated themselves an average of 8.7 points on compliance with COVID-19 measures. It was found that the participants had a 55% confidence in the Coronavirus Scientific Advisory Board (Turkey) and the World Health Organization (WHO) regarding COVID-19. Conclusions: Like all over the world, health authorities also in Turkey have taken several measures in the context of fighting against the pandemic and they expect society to comply with these measures. The fact that individuals in the society fulfill their individual responsibilities by confirming the accuracy of the information took place in printed/visual and social media from reliable sources is an important factor in reducing the effects of infectious diseases.